Pemodelan dan Simulasi Robot Lengan 3 DOF Menggunakan V-REP - AZ Uchrowi; Lasmadi Lasmadi; Sutjianto Soekarno (Institut Teknologi Dirgantara Adisutjipto, 2019)
Movement of objects from one position to another position is usually by conventional method of human strength. Development of robotics technology makes movement of objects in the industry by arm robot system. By using arm robot system, the work more effective. The aim of this reaserch is to modeling 3 Degree of Freedom arm robot with kinematics method using V-REP software. Kinematics method is a subject that analyze robot movement without knowing the force that causes the movement. This research use the forward kinematics method so that arm robot can reach the goals. The input from this robot is an angle which is computed using the forward kinematics method. The output is an end-effector coordinate. Based on the result of the research, the 3 Degree of Freedom arm robot is capable to move the object from one position to another position and an error that occurs can achieve 4,99% for x coordinate, 5,57% for y coordinate, and 3,18% for z coordinate. Based on these results, the 3 Degree of Freedom arm robot with the forward kinematics method can be simulated in V-REP software effectively.